Potential Subsurface Lava Tube Skylight on the Western Flank of Elysium Mons, Mars - Ravi Sharma; Chunyu Ding; Yan Su; Zhonghan Lei; Changzhi Jiang; Jiangwan Xu; YuXiao Zhi; Zihang Liang; Jiawei Li; Xiaohang Qiu; Haoyu Chen; S. N. A. Jaaffrey; et al. (The Astronomical Journal)
The western flank of Elysium Mons, Mars, hosts a potential cave candidate (PCC) associated with a partially collapsed pit chain, previously identified in the Mars Cave Catalog. This study presents the first comprehensive investigation of the PCC, employing high-resolution imagery, thermal observations, topographic, geological, and mineralogical analyses to evaluate its structure and resource potential, and hypothesized to connect to a potential subsurface lava tube cave. High-resolution imagery from CTX and HiRISE on board the Mars Reconnaissance Orbiter (MRO), captured across varying solar angles, reveals an elliptical structure with constant shadowed regions and partial roof collapse, suggesting significant depth and consistency with a Potential Subsurface Lava Tube Skylight. Unlike the adjacent pit chain, which cools rapidly at night due to the lack of subsurface connectivity, the PCC retains heat and shows warmer appearance, indicating connectivity with the subsurface cave environment. Thermal observations from THEMIS on board Mars Odyssey confirm a pronounced night-time thermal anomaly, while topographic data from Mars Orbiter Laser Altimeter on board Mars Global Surveyor (MGS) provide detailed elevation profiles. Mineralogical analysis using Gamma-Ray Spectrometer data from Mars Odyssey identifies geochemical signatures indicative of the presence of olivine and pyroxene, iron oxides, feldspars, and potential volcanic glass. The PCC’s unique morphological, thermal, and mineralogical characteristics, along with cave entrance identification and insights from the conceptual model, highlight a potential environment for astrobiological investigations. These findings, derived from integrated data sets across MRO, Mars Odyssey, and MGS, provide crucial insights into Martian subsurface processes, resource availability, future human/robotic missions, and the planet’s potential to support life.